Infestation by the Mite, Tyrophagus putrescentiae (Schrank) (Acaridae: Sarcoptiformes), on Dog Treat and Processed Meats: Relative Susceptibility and Protection with Propylene Glycol - Filipi, Cassandra; Phillips, Thomas W. (My University, 2017)
T. putrescentiae is a common pest in dried meats and pet food products where they can reproduce. Propylene glycol (PG) is a food-safe additive known to inhibit mite infestation, but some consumers have considered it as a controversial additive to use in products mainly due to its similarity to the toxic ethylene glycol, which is a key component in anti-freeze (DogFoodAdvisor, 2009). The purpose of experiments here were to evaluate the susceptibility of high-valued dog treats and different aged meats to T. putrescentiae, and then to determine if application of PG reduces infestation to the susceptible foods. Of five different dog treats tested, only one was susceptible to mite infestation and this product had the highest moisture content (28%) of those tested. For dried meats, the Prosciutto and Salami were mildly susceptible compared to the others with no infestation. Dipping the susceptible dog treat in 50% PG prevented mite infestation compared to being dipped just in water. Prosciutto dipped in 50% PG was fully protected from mite infestation. This work confirms that PG can protect foods from mites and its use as a coating, rather than as a complete additive, points to new applications to protect dried meats and pet treats.